Cooper and Gunn's tutorial pharmacy - Carter, S. J. (New Delhi, India : CBS Publishers & Distributors, 2005)
A major feature of this revision is the greater depth to which many of the fundamental aspects of pharmaceutics have been treated.
Part one Physical pharmaceutics -- Part two Pharmaceutical technology -- Part three -- Biological pharmacy
Includes bibliographical references and index.
Keywords: PHARMACY